Pembekalan Kompetensi Tambahan Bagi Fresh Graduate Berbasis Sibima Konstruksi - Mohammad Junaedy Rahman; Ahnaf Riyandirga; M. Reza Hasrul (Sakura Digital Nusantara, 2023)
Companies require high-quality strategic decision-making (SDM) to achieve their goals, remain competitive, and experience rapid growth. Securing employment can be a challenging endeavor for recent graduates. An individual possessing exceptional personal traits and a higher level of competence is regarded as more advantageous to the firm. Fulfilling such standards might be challenging for prospective employees, particularly those who lack experience, such as recent graduates. The main issues are twofold: firstly, the difficulty in effectively developing the human resources required for national construction, which involves costly traditional training methods and limited capacity and scope; secondly, the growing number of undergraduate graduates each year, without a corresponding increase in job opportunities. Additionally, the abundance of quality requirements, specific skills, limited employment options, and intense competition place fresh graduates in need of a labor certificate to validate their qualifications. The primary objective is to enhance the students' comprehension of SIBIMA in order to bolster the number of qualified professionals in the workforce. The employed methodologies include: lectures, talks, training, and questioning. The outcome attained is that the partner has acquired knowledge about SIBIMA to enhance the certified workforce.